The effect of foreign investment flow on commonality in liquidity on the Brazilian stock market - Silva, Claudio Pilar; Machado, Márcio André Veras (Revista Contabilidade & Finanças, 2021)
The aim of this study was to analyze the characteristics and determinants of commonality in liquidity in the Brazilian stock market. Since the internationalization of the Brazilian stock market (Bolsa, Brasil, Balcão – B3), the flow of foreign investment in Brazil has increased over the years, except in times of crisis. Thus, the present study argues that, in the Brazilian stock market, commonality in liquidity is partly determined by foreign investor trading. Despite the benefits obtained from foreign resources in the Brazilian stock market, it is important to analyze the effect of this flow of foreign investment into the Brazilian stock market. This paper contributes to the current literature by providing evidence for commonality in liquidity in the Brazilian stock market and by showing its stronger effect in periods of market decline. Therefore, investors pay greater attention to the risk of commonality in their portfolios when executing orders and to their trading timing due to the increase in transaction costs of the stocks most sensitive to commonality in liquidity. The study sample consisted of a set of companies listed on the Brazilian stock exchange from January 2007 through December 2017. To analyze commonality in liquidity, we used the model proposed by Karolyi, Lee, and Djik (2012) and by Qian, Tam, and Zhang (2014). To measure the influence of foreign investors on the Brazilian stock market, we used three measures based on Gonçalves and Eid (2016). The results showed that commonality occurs in the Brazilian stock market and that it peaks during international financial crises, as well as indicated that commonality might be higher in times of crisis due to capital constraint. In addition, the results showed that foreign investor participation partly determined commonality.